Strategi Pemasaran Daya Tarik Wisata Alas Harus Pasca Pandemi Covid-19 - Kadek Wira Adi Saputra; Pande Putu Juniarta (TOBA: Journal of Tourism, Hospitality, and Destination, 2022)
Alas Harum Bali is an agro-tourism destination that offers various tourist attractions that can attract tourists to visit. The attraction is packaged in the form of natural, artificial, and cultural tourist attractions. As one of the popular tourist destinations in Ubud, it does not rule out the possibility that Alas Harum will not be affected by the Covid-19 pandemic. Alas Harum must temporarily close in 2020. After 2 years of the Covid-19 pandemic, the Alas Harum has started to operate again to receive tourist visits. This study uses qualitative research methods with data collection techniques, namely through observation, interviews and documentation. The data sources used are primary and secondary data sources. Primary data was obtained through interviews with researchers at Alas Harum and secondary data was obtained through other related studies regarding Alas Harum Agrotourism. The results of this study show several marketing strategies carried out by managers of the Alas Harum tourist attraction after the Covid-19 pandemic including Partnerships, Collaborating with Influencers, Involving Employees and Maintaining Old Customers.